O-135 Long term secondary efficacy of linzagolix for heavy menstrual bleeding (HMB) due to uterine fibroids (UF): 52-week results from two placebo-controlled, randomized, phase 3 trials. (6th August 2021) - Taylor, H; Donnez, J; Petraglia, F; Gemzell Danielsson, K; Renner, S; Bestel, E; Gotteland, J P; Humberstone, A; Garner, E
Abstract: Study question: Are symptomatic improvements in women with UF observed after 24 weeks of linzagolix treatment with or without add-back therapy (ABT) maintained over 52 weeks? Summary answer: Improvements in anemia, pain and quality of life previously reported at 24 weeks were maintained at 52 weeks. What is known already: We previously reported that partial or full suppression of estradiol (E2) with once daily doses of either 100 or 200 mg linzagolix for 24 weeks, with or without ABT, were effective in reducing heavy menstrual bleeding associated with uterine fibroids, improving other symptoms such as pain and anemia and improving quality of life. Here we report the maintenance of effect on secondary endpoints after 52 weeks of treatment. Study design, size, duration: Linzagolix is an investigational, oral GnRH antagonist being developed to treat HMB due to UF. PRIMROSE 1 (P1, USA, NCT03070899) and PRIMROSE 2 (P2, Europe and USA, NCT03070951) are randomized, double-blind, placebo-controlled Phase 3 trials, with essentially identical design, investigating the efficacy and safety of linzagolix with and without hormonal add-back therapy (ABT: 1 mg estradiol/0.5 mg norethindrone acetate) once daily for 52 weeks. Participants/materials, setting, methods: Participants had HMB due to UF (>80mL menstrual blood loss (MBL)/cycle) and were equally randomized to: placebo, linzagolix 100mg, linzagolix 100mg+ABT, linzagolix 200mg, or linzagolix 200mg+ABT. After 24 weeks, subjects originally randomized to placebo or linzagolix 200mg were switched to linzagolix 200mg+ABT except in P1 where 50% placebo subjects continued placebo until 52 weeks. Secondary efficacy assessments included hemoglobin, pain (0–10 numeric rating scale) and health related quality of life (HRQL) on the UF-QoL questionnaire. Main results and the role of chance: P1 trial subjects (n = 526) had a mean age of 42 years, pain score of 6.6 and HRQL total score (0–100) of 36.4 and 63% were Black. P2 trial subjects (n = 511) had a mean age of 43 years, pain score 4.8 and HRQL total score of 46.1 and 5% were Black. Mean baseline MBL was about 200 mL per cycle in both studies. In both trials, significant improvements compared to placebo observed at week 24 for secondary endpoints, including pain, anemia and QoL in all linzagolix treatment groups were maintained at 52 weeks. Mean±SD hemoglobin levels in anemic patients (<12 g/dL) increased from baseline by 1.7±1.9, 1.9±1.7, 2.2±2.4, 2.7±1.9 in P1 and 1.2±1.9, 2.9±1.8, 2.4±2.1, 3.0±1.4 in P2 in the 100mg, 100mg+ABT, 200mg/200mg+ABT, 200mg+ABT groups, respectively, compared to 0.6±1.8 with placebo (P1). Mean±SD change from baseline in pain scores were -3.3±3.1, -2.7±3.2, -2.6±3.0, -3.9±3.2 in P1 and -2.6±3.1, -2.6±2.8, -3.0±2.6, -2.8±3.0 in P2 in the 100mg, 100mg+ABT, 200mg/200mg+ABT, 200mg+ABT groups, respectively, compared to -0.4±2.5 with placebo (P1). Mean±SD change in HRQL total scores were 25.0±26.2, 34.2±30.1, 29.7±29.2, 38.3±29.2 in P1 and 16.8±24.0, 29.6±23.2, 31.9±26.8, 30.7±26.0 in P2 in the 100mg, 100mg+ABT, 200mg/200mg+ABT, 200mg+ABT groups, respectively, compared to 14.6±23.9 with placebo (P1). Limitations, reasons for caution: Here we report data in both trials up to 52 weeks of treatment. No statistical comparisons were done at 52 weeks (the primary analysis was done after 24 weeks treatment). Post-treatment follow-up will provide more information in symptom recurrence after stopping treatment. Wider implications of the findings: All linzagolix treatments provided sustained benefit. Two regimens previously identified for potential long-term treatment, 200mg with ABT and 100mg without ABT, provided sustained improvements of anemia, pain and associated quality of life. These different treatment regimens could be important to address the diverse needs of women suffering from uterine fibroids. Trial registration number: ClinicalTrials.gov: NCT03070899, NCT03070951